An Economic Analysis of Milk Production of Buffalo and Cow in Rajasthan - Meena, G L; Sharma, Latika; Mishra, Siddhartha; Choudhary, Suraj (Indian Journal of Animal Nutrition, 2019)
The present research study was conducted in Rajasthan during the year 2017-18. An attempt has been made in this investigation to work out the cost and returns from milk production across different milch species of animals.  The study covered 60 dairy households from Jaipur and Alwar districts were selected purposively from Rajasthan on the basis of highest livestock population in the state. The results of the study revealed that the average size of herd (standard animal units) of households surveyed was 6.68 and majority of them was buffalo followed by young stock, crossbred cow and local cow. Average investment per household in was ₹ 269455 per annum and the major expenditure was on milch animals (₹ 198842) followed by cattle shed and stores (₹ 59475) and dairy equipments (₹ 11138). Average milk yield per day per animal was highest for crossbred cow (7.22 litres) followed by buffalo (5.49 litres) and local cow (3.98 litres). Net maintenance cost per milch animal per day was found to be relatively higher in case of crossbred cow (₹ 151.51) followed by buffalo (₹ 148.91) and local cow (₹ 119.68). The per litre cost of milk production was observed to be higher in case of local cow (₹ 30.07) followed by buffalo (₹ 27.12,) and crossbred cow (₹ 21.04). The net income per day was relatively higher in case of buffalo (₹73.44) compared to crossbred cow (₹ 23.18), while it was found negative for local cow (-4.86).